Caring for the heart : Mayo Clinic and the rise of specialization - Fye, Bruce; Mayo Foundation for Medical Education and Research ([New York] : Oxford University Press, 2015)
This online resource weaves together the major developments in the diagnosis and treatment of heart disease in the twentieth century, how the Mayo Clinic evolved from a family practice in Minnesota into one of the world's leading medical centres, and how the invention of new technologies and procedures promoted specialisation among physicians and surgeons. Patient stories and media perspectives are included throughout, as are carefully chosen references that offer greater detail and additional perspectives.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 24, 2016).
Keywords: Mayo Clinic -- History; Cardiology -- Minnesota -- History; Cardiology